CHINESE AND SLAVIC CULTURE DIFFERENCES FOR CHINESE LANGUAGE TEACHING IN UKRAINE - Yuxiangt , Xiong (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
Teaching Chinese as foreign language is not only a language teaching, but also a cultural teaching. To teachers, the teaching objects are foreigners who have different cultural backgrounds. To learners, it is a social cultural communication. There are lots of differences between Chinese and Slavic cultures, which have great impact on language learners. That is to say, teachers need to consider the differences and adopt effective measures to help Ukraine students grasp Chinese. Language is the carrier of culture, and language itself is also an important part of culture. "Teaching Chinese as a Foreign Language" is both a language teaching and a kind of cultural teaching. The unity of language teaching and cultural teaching is the most fundamental characteristic of teaching Chinese as a foreign language. The core and purpose of teaching Chinese as a foreign language is to cultivate students’ communicative competence in Chinese. For students whose native language is non-Chinese, this communicative competence in Chinese is a cross-cultural communication ability. The system of kinship terms represents the traditional culture of any nation and reflect the historical accumulation of different titles, respectively, represent different language culture. Kinship terms, as a basic vocabulary in a tight form of the national language system. relatively stable, reflecting a social life of nations, cultural traditions, national psychology and so on. Although there are similarities between ethnic and national phenomenon, but similar does not mean exactly the same, there are some difference to identify those key kinship. ___________ REFERENCES • Kolesov, V. Kul’tura rechi. Kul’tura povedenija (Leningrad, Lenizdat, 1988), 271 (In Russ.). • Krongauz A. «Obrashhenie kak sposob modenirovanija kommunikativnogo prostranstva.» Logicheskij analiz jazyka. Obraz cheloveka v kul’ture i jazyke (1999): 124-134 (In Russ.). • Ryzhova, P. «Obrashhenie kak komponent kommunikativnogo akta.» Avtoref. kand. filol. nauk (Kalinin, 1982) (In Russ.). • 杜学增. 中俄文化习俗比较 [Du Xuezeng. Comparison of Chinese and Russian cultural customs (1999) (In Chinese). • 刘焕辉. 交际语言学导论 [Liu Huanhui. Introduction to Communicative Linguistics] (1992) In Chinese)/ • 祝畹瑾.社会语言学概论 [Zhu Wanjing. Introduction to Sociolinguistics] (1992) (In Chinese).